Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21276/ijcmr.2019.6.7.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Demographic Profile of Skin Disorders in School- Going Children of Urban and Rural Jaipur

Abstract: Introduction: Skin disorders are common in children but have not been regarded as a public health problem even though they put a large burden on health care systems worldwide. About one-third of children in India are affected by skin disorders at any given time. Climatic factors, poor hygiene, poor access to water, household overcrowding and close contact lead to this high prevalence. However there is a relative paucity of data in comparison to this high prevalence. Study objective was to determine the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
(28 reference statements)
3
8
0
Order By: Relevance
“…This is similar to previous studies. 5 The sex distribution in our study shows a slight female preponderance similar to reported by earlier studies like Karthikeyan et al 14 Most other studies suggest equal or slight male preponderance. 1 Out of 72 cases of dermatoses in the hospital, the age group mostly affected is primary school with 48.6%, and high school group comprising of 26.4%.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is similar to previous studies. 5 The sex distribution in our study shows a slight female preponderance similar to reported by earlier studies like Karthikeyan et al 14 Most other studies suggest equal or slight male preponderance. 1 Out of 72 cases of dermatoses in the hospital, the age group mostly affected is primary school with 48.6%, and high school group comprising of 26.4%.…”
Section: Discussionsupporting
confidence: 91%
“…This is identical to 58% reported by Kohli et al which was conducted in Jaipur. 5 Even the prevalence of infectious dermatoses (~50%) correlates to previous published results. 1,12 Our findings of infectious dermatoses being due to parasitic infestations, more in females and primary school group validates the findings of previous studies.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations